Decentralisation in developing countries - Meenakshisundaram, S. S. (New Delhi, 1994)
The book is a comparative study on the decentralization patterns in thre developing countries of comparable size and population-Nigeria, China and India.
Keywords: Decentralisation-Developing Countries